Comparison of Juvenile and Adult Onset Refractory Spondyloarthritis Patients Attending a Tertiary Rheumatology Clinic (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Objectives: To compare the demographic and clinical characteristics of juvenile onset refractory spondyloarthritis (JOSpA) with a group of adult-onset refractory spondyloarthritis (AOSpA) patients.Methods: In this real-life, cross-sectional study, a total of 215 SpA patients (refractory to two NSAIDs and/or DMARDs) were enrolled following ASAS classification criteria from a rheumatology center in Dhaka, Bangladesh. Based on age, the patients were divided into JOSpA group and AOSpA group for analysis. The patients’ demographics, quality of life, laboratory and clinical characteristics were compared and analyzed between the two groups using chisquare and independent sample t-test.Results: Among 215 patients, 57 (53 males, 4 females) were in JOSpA group, and 158 (126 males, 32 females) were in AOSpA group. Most patients were male in both groups (P=0.02). The mean age at diagnosis for JOSpA and AOSpA were 27.68±9.5 and 40.28±10 years respectively (P=0.00), and mean age at onset of disease in JOSpA and AOSpA were 12.33±3.62 and 29.58±96.5 years respectively. The mean disease duration was 15.36±9.3 months in JOSpA compared to 10.70±7.1 months in AOSpA group (P=0.00). Sixteen (28.1%) JOSpA and 9 (5.7%) AOSpA patients were undernourished, (P=0.00). On the contrary, obesity was more prevalent in AOSpA patients (41.1%) than those in JOSpA patients (21.1%) (P=0.00). There were significant differences in mean haemoglobin (11.38±1.7 and 10.94±1.3 g/dl) (P=0.05) and mean serum creatinine (0.94±0.2 and 0.86±0.2 mg/dl) (P=0.03) levels in AOSpA and JOSpA groups respectively. HLA-B27 was done in 20 JOSpA and 61 AOSpA patients. Among them, 19 (95%) were positive in JOSpA and 55 (90.16%) were positive in AOSpA groups. Similarly, hips involvement was higher in JOSpA group 19 (33.3%) compared to the AOSpA group 21 (13.3%) (P=0.004). Significant differences were observed in mean disease activity parameters, patient global assessment (PGA) (7.86±1.2 vs 7.38±1.4, P=0.02), ASDAS-CRP (4.60±0.8 vs 4.33±0.9, P=0.05), and ASDAS-ESR (4.49±0.8 vs 4.17±1.0, P=0.02) in JOSpA and AOSpA groups respectively. The modified Stoke AS Spinal Score (mSASSS) in AOSpA group was higher (24.18±17.22) than that of JOSpA group (17.10±9.6) (P=0.00).Conclusions: In JOSpA patients, under nutrition, hip involvement, longer disease duration, uveitis, PGA, low Hb level and ASDAS-ESR disease activity scores were higher. On the contrary in AOSpA group, male gender, married subjects, obesity, higher creatinine level and mSASSS scores were higher.J Bangladesh Coll Phys Surg 2020; 38(2): 79-85